A note on the max-sum equivalence of randomly weighted sums of heavy-tailed random variables - Yang, Yang; Wang, Kaiyong; Leipus, Remigijus; Šiaulys, Jonas (Nonlinear Analysis: Modelling and Control, 2013)
This paper investigates the asymptotic behavior for the tail probability of the randomly weighted sums ∑k=1nθkXk and their maximum, where the random variables Xk and the random weights θk follow a certain dependence structure proposed by Asimit and Badescu [1] and Li et al. [2]. The obtained results can be used to obtain asymptotic formulas for ruin probability in the insurance risk models with discounted factors.